Konsep Diri Siswi melalui Kelompok Acuan di SMA Tarakanita 1 Jakarta - Ayuningtyas, Anastasia; Nugroho, Wahyu Budi; Zuryani, Nazrina (Program Studi Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Udayana, 2019)
ABSTRACT This study is to describe the types of reference groups in Tarakanita 1 Senior High School, while knowing how the development of self-concepts possessed by female students based on the behavior emulated through the reference group. This research is qualitative with descriptive-explanative type and analyzed using the theory of the looking glass self from Charles Horton Cooley. Based on the research that has been done, female students try to imagine about themselves from other people's minds. People around female students expecting that they have a good attitude. Then female students gather information about what should be done to be able to behave as others think. The information that obtained by female students through attitudes and behaviors that can be emulated from several reference groups. Last, female students describe the information they get as a basis for developing their self-concept, namely feeling comfortable and happy because it has positive impact. Keywords; Self-Concept, Female Students, Reference Group.